Paradigma Pemikiran Pendidikan Multikultural Menurut KH. Abdurrahman Wahid - Wijaya, Muhamad Rudi; Habibi Ritonga, Anas; Subekti, Subekti (Studi Multidisipliner: Jurnal Kajian Keislaman, 2021)
Indonesia which is a multicultural country with various socio-cultural, ethnic, religious, geographical conditions, customs. This fact becomes a distinctive feature of plural pluralism if people are side by side, complement each other, respect each other, and are able to adapt. The development of education in Indonesia cannot be separated from religious leaders who are role models for most Indonesian people. Which makes one of the highlights or views of the results of education such as the Islamic figure KH Abdurahman Wahid. This research is a type of qualitative research that explores data by reviewing the literature. Data analysis used is tracing primary and secondary sources, classifying data based on research formulas, processing data/quoting displaying data, data abstraction, data interpretation, and conclusions. The results of the study show that the paradigm in education is shown from various aspects including in the socio-cultural community, religion and politics. These three things must go hand in hand to realize a successful education in the presence of diversity in Indonesia